(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The hybrid design of Cooling and air-conditioning establishes the main consumers of building energy in areas branded by hot and cold climatic circumstances. The examined design includes six unit components: compressor, shell-and-tube heat exchanger, expansion valve, a coil-and-tank, a vacuum collector, and a solar power. Several experiments were conducted by methodically changing important working limits to measure their effect on the thermal presentation of the hybrid design system. The inspected limits comprised cooling discharge (2, 3, 4, and 5 L/min), temperature (14, 12, 10, and 8 °C), refrigerant mass rate (70, 50, and 30 kg/h), tank temperature (80, 75, and 70 °C), and solar light intensity under the meteorological conditions of Muthanna in Iraqi. The results exposed that the design’s presentation declines with an increase in temperature from 8 °C to 14 °C, the coefficient of performance (COP) lower from 2.8 to 1.98, accompanied by an increase in consumption of compressor power from 650 W to 980 W. Also, the thermal performance of the design was found to be markedly affected by the cooling water discharge. An improvement in discharge led to a consistent development in the COP. When the cooling discharge increased from 2 L/min to 6 L/min, the COP improved from 2.6 to 3.2, though consumption of compressor power reduced from 1050 W to 670 W.